Report of the Working Group on Training for Development Administration in the Seventh Plan (1985-90) - Planning Commission (Planning Commission Government of India, 1984)
The Report on Training for Development Administration during the Seventh Five-Year Plan (1985–90) evaluates and proposes enhancements to training programmes for government personnel in India. Building on initiatives from the Fifth and Sixth Plans, the report emphasizes expanding training beyond senior officials to include middle and lower-level officers who play crucial roles in planning, project execution, and development administration. Key achievements include the projected training of over 11,000 officers and significant improvements in training infrastructure and library resources at state-level institutions. Recommendations focus on district-level, context-specific training, specialized programmes, training of trainers, and the development of advanced instructional materials. Additionally, informal training through correspondence courses and research initiatives to assess training effectiveness are proposed. A total budget of Rs. 6.5 crores is suggested to implement these initiatives, with allocations for specialized programmes, hardware and software resources, and projects targeting underserved regions. The report underscores the importance of dynamic, practical, and locally relevant training strategies to enhance administrative efficiency, strengthen public sector performance, and ensure effective execution of development projects, thereby aligning training efforts with the overarching goals of the Seventh Five-Year Plan.
Government of India Planning Commission October-1984
Keywords: Development Administration; Training Programmes; Public Sector; District-Level Training; Officer Capacity Building; Training Infrastructure; Seventh Five-Year Plan; Training of Trainers; Resource Enhancement; Administrative Efficiency; Project Implementation; Research Funding